Hakikat Masyarakat dan Implikasinya dalam Filsafat Pendidikan Islam - Zaimah Zahirah Lubis; Meyniar Albina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Society is often seen as a collective of individuals who share similar goals and characteristics. Every individual in an Islamic society has equal rights and obligations, without the existence of a caste system; Priority is only determined by the level of piety they have to Allah. The basic characteristics of Islamic society can be categorized into three main characteristics: surrender to Allah, emphasis on devotion, and the practice of mutual respect. Fraternity, compassion, equality, freedom, and social justice are fundamental foundations in the Islamic community. The philosophy of Islamic education and society are closely interconnected, like an inseparable symbiosis. Therefore, the Muslim community plays a crucial role and has the responsibility to build a stable Islamic society, a civilized Islamic society, and an ideal Islamic society, in line with the teachings of the Qur'an and As-Sunnah.